Revisiting the role of linguistic complexity in ESL reading comprehension - Barrot, Jessie Saraza (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
This study investigated the two linguistic compone nts positioned at the two ends of the continuum that influence ESL reading comprehension: lexical and syntactic features. Specifically, the present study aims to determine these two linguistic features of the texts most comprehensible to pupils. Sixty pupils from three grade levels (2,4, and 6) were asked to read four texts with varying text difficulty level from which the most comprehensible text per grade level was identified after a comprehension test. The findings revealed that the pupils reading comprehension progressed as they advance in grade level. Moreover, the findings revealed that the lexical feature of the reading texts becomes more complex as grade level advances. This indicates that lexical features is a viable factor in determining the readability of the text; that is, as the lexical features of a reading text becomes more complex, the more difficult it is for learners to process such texts for comprehension. Unlike lexical features, the syntactic features of the selected reading texts exhibited an erratic pattern indicating that such features may not be a crucial factor in text readability and in reading comprehension as a whole.